Knowledge Management Strategies in Creating World Class University; Vision 2020: Innovation Management, Development Sustainability, and Competitive Economic Growth - Kornienko A. A. Anna Anatolievna; Kabanova N. N. Natalia Nikolaevna; Nikitina Yu. A. Yulia Anatolyevna; Sakharova E. T. Elena Tarasovna (2016, 2016)
At the end of the XXth and at the beginning of the XXI century university occurred in the condition of a new type of cultural development. As a result, the university becomes the center for producing and reproducing knowledge in knowledge-based society. The aim of the paper is to study the role of the knowledge management in the sphere of university education and the meaning and mechanisms of adaptation in situation when the environment is differed with high level of dynamics and risks complexity To succeed the aim of the study we analyze the process of formulating management cognitive strategies in knowledge society. This study reveals their specifics and defines their potential. The meaning of management is disclosed by means of using the knowledge of massifs as the resource possessing a capability of relevant impact. This paper considers the thesis that the problem of inevitable knowledge obsolescence can find the effective solution by means of appealing to mechanisms of innovative development. We have proved that assessment of a role of innovations offered in the problem field of cognitive management creates prerequisites for relevant assessment of knowledge as a dominating factor of social development, which allows to estimate adequately the status of knowledge in increasing value of knowledge -based capital of a personality. Knowledge society is the resource of developing social and cultural spheres.